Mission unstoppable - Gutman, Dan (Gutman, Dan. Genius Files, 2011)
On a cross-country vacation with their parents, twins Coke and Pepsi, soon to be thirteen, fend off strange assassins as they try to come to terms with their being part of a top-secret government organization known as The Genius Files.